The Potential of Gastronomic Tourism Travel Patterns in Bandung Regency - Meilina, Nabila; Turgarini, Dewi; Pratami Putri, Dias (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2024)
Bandung Regency, located in West Java, has significant tourist potential, thanks to the beauty of the mountains and plantations that produce a variety of local commodities as well as traditional food and beverages. Although tourism in Bandung regency is quite developed, the Regional Government noted that there are some problems in the development of tourism, among them are low tourism contribution to the PDRB and the lack of superior tourist destinations in some areas. One of the tourist potential that can be used as an outstanding tourist in Bandung regency is a gastronomic tour. Turgarini (2018) stated that gastronomic tourism has the potential to generate additional income in the region by highlighting its typical food as a magnet for tourists. At present, however, the management of traditional food and gastronomic tourism patterns in the region are not well structured because the government is more focused on the development of natural and cultural tourism. The research is aimed at identifying potential attractions, mapping, as well as designing travel patterns and gastronomic tour packages in Bandung Regency. The method used is qualitative descriptive with data collection techniques such as interviews, observations, literature studies, and documentation, as well as determination of participants using snowball sampling techniques and purposive samplings. This research found various tourist attractions such as Kalua Jeruk, Rudjak Ciherang, and Borondong that can be developed into a gastronomic tour by producing two kinds of tourist packages in Bandung Regency. It is expected that the maps and gastronomic tour packages generated can help stakeholders in managing and developing these packages to attract local, national, and international tourists.